PENGARUH CURRENT RATIO, TOTAL ASSET TURN OVER, DAN NET PROFIT MARGIN TERHADAP RETURN ON ASSET PADA PERUSAHAAN SUBSEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI PADA TAHUN 2012-2016 - eria pratikaning tyas (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
The purpose of this study is to describe To understand (1) the influence of current ratio, total asset turnover, net profit margin collectively to return on aseet, (2) influence of current ratio to return on aseet (3) influence of total asset turnover to return on aseet (4) the influence of net profit margin on return on aseet (5) how many independent variables can explain variable Dependent Sampling technique used is purposive sampling with criteria of food and beverage subsectors listed on BEI which always present financial report during observation period (2012-2016). The analysis technique used is multiple regression analysis and hypothesis test using f test in silmutan, t test partially with level of significance 5% and test of coefficient of determination. This research uses correlational method that relate a variable with other variables to understand a phenomenon by determining the level or degree of relationship among the variables. The sample used by purposive sampling is netode known before. From the analysis result shows CR, TATO, and NPM in silmutan have an effect on to ROA at company of food and beverage sub sector at year of BEI 2012-2015 at singnifikansi value less than 0,05 or 5%. While partially variable CR influence negate but not singnifikan to ROA because with value of beta equal to -0,006 and significance value equal to 0,921 value singnifikansi that> 0,05 or 5%, But variable of TATO and NPM have positive influence to ROA with value of TATO beta equal to 0,670 and a significance value of 0,000 NPM beta value of 1.115 and a singularity value of 0,000 because the singnifique value is less than 0.05 or 5%. The value of determination coefficient (Adjusted R Square) is 0.903 or 90.3% so it can be stated that the independent variable (current ratio, total asset turnover, and net profit margin) in explaining the variation of the dependent variable (return on asset) is 90.3 % and the rest of 9.7% explained by other variables outside the regression model Suggested for further researcher adds research variables, time period and reproduce samples, in order to obtain more accurate test results. Keywords: current ratio (CR), total asset turnover (TATO), net profit margin (NPM), and retrun on asset (ROA).